A randomized trial of two home-based exercise programmes to improve functional walking post-stroke - Mayo, Nancy E; MacKay-Lyons, Marilyn J; Scott, Susan C; Moriello, Carolina; Brophy, James (Clinical rehabilitation, 2013)
Objective: To estimate the relative effectiveness in improving walking ability and other mobility and health outcomes post-stroke of two home-based exercise programmes – stationary cycling and an exercise and walking programme. Design: An observer-blinded, randomized, pragmatic, trial with repeated measures. Setting: Hospital centers in two Canadian cities. Subjects: People within 12 months of acute stroke who were able to walk >10 meters independently and healthy enough to engage in exercise. Interventions: Two dose-equivalent interventions, one involving stationary cycling and the other disability-targeted interventions were tested. Both protocols required daily moderate intensity exercise at home building up to 30 minutes per day. One group exercised on a stationary bicycle, the second group carried out mobility exercises and brisk walking. Main measures: The primary outcome was walking capacity as measured by the six-minute walk test (6MWT). Secondary outcomes were physical function, role participation, health-related quality of life exercise adherence, and adverse events. Results: The study failed to meet recruitment targets: 87 participants (cycle group, n = 43; exercise group, n = 44) participated. No significant effects of group or time were revealed for the 6MWT, which was approximately 320 m at randomization. A significant effect for role participation was found in favor of the exercise group (global odds ratio (OR) for cycling vs. exercise was 0.51; 95% confidence interval (CI), 0.27–0.95). Change in the 6MWT between highest and lowest adherence categories was statistically significant (p = 0.022). Conclusions: Both programmes were equally effective in maintaining walking capacity after discharge from stroke rehabilitation; or were equally ineffective in improving walking capacity. Clinical Trials Gov number: NCT00786045.